Winter and spring long-term dynamic of air temperature in Central Ukraine - Helevera, Olha; Mostipan, Mykola; Topolnyi, Sergii (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2023)
This study aimed to analyze data from meteorological stations in central Ukraine that have the longest observation period and to search for patterns in the dynamics of temperature indicators over the past 140-200 years. Data and methods. To characterize the climate of central Ukraine, we analyzed the average monthly and average annual temperatures of Uman, Kropyvnytskyi, and Poltava, which have the longest continuous or almost continuous periods of observation. Based on these data, we have constructed graphs of changes in the average annual and average monthly temperatures for the winter and spring seasons. To analyze the dynamics of temperature indicators, we built linear and 11-year moving averages. The results. The analysis of meteorological data from weather stations in central Ukraine over the entire period of observation showed the following: average annual temperatures increased from 1.4 degrees in Kropyvnytskyi, 1.6 degrees in Uman to 2.5 degrees (since 1886 - 2.2 degrees) in Poltava. The highest average annual air temperatures at all weather stations were recorded in 2020 and 2021. The largest temperature increase occurred in the winter months. Over the entire observation period, the average monthly temperature in December increased by 2.0 degrees in Kropyvnytskyi, 2.3 degrees in Uman, and 3.6 degrees in Poltava (3.3 degrees since 1886). The average monthly temperature in January increased from 2.4 degrees in Uman and Kropyvnytskyi to 4.9 degrees (3.5 degrees since 1886) in Poltava. The average monthly temperature in February increased from 2.2 degrees in Kropyvnytskyi, 3.4 degrees in Uman to 4.1 degrees (since 1886 - 2.9 degrees) in Poltava. All three weather stations have common periods of rising and falling temperatures, with an increase in the average monthly temperature in the winter months from 1987-1989 to 2022. The air temperature in the spring months also increased significantly. Over the entire observation period, the average monthly temperature in March increased from 2.3 degrees in Kropyvnytskyi, 3.0 degrees in Uman to 3.6 degrees (since 1886 - 3.5 degrees) in Poltava. The average monthly temperature in April increased from 2.1 degrees in Kropyvnytskyi, 2.4 degrees in Uman to 4.2 degrees (since 1886 - 3.4 degrees) in Poltava. The average monthly temperature in May increased from 0.5 degrees in Uman and Kropyvnytskyi to 2.9 degrees (since 1886 - 1.3 degrees) in Poltava. All three weather stations have common periods of rising and falling temperatures, with a slight increase in average monthly spring temperatures from 1988-1990 to 2022. Analyzing the graphs of 11-year moving averages, one can notice the presence of periods of increase and decrease in average monthly temperatures lasting about 33 years or doubled periods lasting about 66 years. Scientific novelty. For the first time, the data of weather stations in central Ukraine for the entire period of observation (138 years – Uman, 148 years – Kropyvnytskyi, 198 years – Poltava) were analyzed and regularities in the dynamic of temperature indicators were determined. The practical significance lies in the possibility of using the researchers results to predict future climate change.